Ameliorated immunity elicited by intradermal inoculation in individuals vaccinated with inactivated SARS-CoV-2 vaccine. Issue 48 (26th November 2021) - Fan, Shengtao; Li, Dandan; Zhao, Heng; Yu, Li; Cui, Pingfang; Wang, Lichun; Zhang, Ying; Liao, Yun; Xu, Xingli; Jiang, Guorun; Li, Qihan
Highlights: SARS-CoV-2-specific antibodies were eliminated six months after immunization. SARS-CoV-2-specific immune response activated by intradermal inoculation. SARS-CoV-2 antibodies can maintain for 6 months after stimulation. Abstract: In clinical trials, antibodies against SARS-CoV-2 were almost eliminated in participants six months after immunization with an inactivated SARS-CoV-2 vaccine. The short duration of antibody persistence is an urgent problem. In this study, the problem was solved by intradermal inoculation with trace antigen. Within 72 h after intradermal inoculation, slight inflammatory reactions, such as redness and swelling, were observed at the inoculation site of the participants. On the 7th, 60th and 180th days after inoculation, the antibodies of the participants were detected, and it was found that the neutralizing antibody and ELISA (IgGs) anti-S antibody levels rapidly increased and were maintained for 6 months. These results indicate that there was a SARS-CoV-2-specific immune response in the participants immunized with an inactivated SARS-CoV-2 vaccine, which could be quickly and massively activated by intradermal trace antigen inoculation to produce an effective clinically protective effect.